Gasdermin D and Beyond – Gasdermin-mediated Pyroptosis in Bacterial Infections. Issue 4 (28th February 2022) - Booty, Lee M.; Bryant, Clare E.
Graphical abstract: Highlights: Many bacteria induce gasdermin-driven host cell pyroptosis which can be a mechanism for removal of the pathogen. Gasdermin D driven pyroptosis may be important in driving the severe inflammation seen in sepsis. Gasdermins have direct and indirect anti-bacterial actions. The diversity in gasdermin expression between animal species may have important implications for zoonotic pathogen carriage. Abstract: The discovery of pyroptosis and its subsequent implications in infection and immunity has uncovered a new angle of host-defence against pathogen assault. At its most simple, gasdermin-mediated pyroptosis in bacterial infection would be expected to remove pathogens from the relative safety of the cytosol or pathogen containing vacuole/phagosome whilst inducing a rapid and effective immune response. Differences in gasdermin-mediated pyroptosis between cell types, stimulation conditions, pathogen and even animal species, however, make things more complex. The excessive inflammation associated with the pathogen-induced gasdermin-mediated pyroptosis contributes to a downward spiral in sepsis. With no currently approved effective treatment options for sepsis understanding how gasdermin-mediated pyroptotic pathways are regulated provides an opportunity to identify novel therapeutic candidates against this complex disease. In this review we cover recent advances in the field of gasdermin-mediated pyroptosis with a focus on bacterial infection and sepsis models in the context of humans and other animal species. Importantly we also consider why there is considerable redundancy set into these ancient immune pathways.